Enhancing genetic transformation efficiency of melon (Cucumis melo L.) through an extended sucrose-removal co-culture - Li, Xiang (2025)
In plants, Agrobacterium-mediated transformation (AMT) is a valuable technique for characterizing gene function and developing varieties with new traits. However, melon, as a cash crop, has proven to be recalcitrant to AMT. During AMT, the co-culture phase is crucial for the successful integration of T-DNA into the host genome by Agrobacterium tumefaciens (A. tumefaciens). To enhance the AMT efficiency in melon, we optimized the co-culture regime by extending the co-culture duration and removing sucrose from the medium. Extending the co-culture duration to 7 days, compared to the usual 2 to 4 days, allowed A. tumefaciens to infect melon explants at its optimal capacity. The removal of sucrose not only prevented excessive proliferation of A. tumefaciens during the extended culture but also reduced the triggering of a defense response in melon explants. Compared to the sucrose-addition co-culture for 4 days, sucrose-removal co-culture for 7 days increased the efficiency of melon transformation by 14 folds. In addition, this optimized co-culture has a synergistic effect with AtGRF5 overexpression on enhancing AMT in melon. Using this optimized transformation protocol, we successfully obtained tendril-less melon plants by knocking out CmTCP1 gene via gene editing, which holds significant breeding potential. The transformation method detailed in this study may serve as a robust tool for gene biology research and plant breeding in melons and may potentially lead to enhanced AMT in other plant species.